Peningkatan Pengelolaan Bank Sampah dalam Upaya Meningkatkan Kesejahteraan Masyarakat di Desa Cicalengka Kabupaten Tangerang - Abdullah Abdullah; Shella Puspita Sari; Aprilia Astuti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Waste management through community-based initiatives such as waste banks plays a significant role in improving environmental quality and economic welfare. This Community Service Program (PKM) titled “Improving Waste Bank Management to Enhance Community Welfare in Cicalengka Village, Tangerang Regency” was carried out to strengthen the management capacity of Bank Sampah Sinaran Mentari. The program aimed to increase the knowledge, skills, and awareness of the community in managing waste more effectively to generate economic value and support environmental sustainability. The PKM activity was conducted on November 2, 2025, involving eight lecturers from Universitas Pamulang as facilitators and forty-nine participants who are members of the waste bank in Cicalengka Village. The implementation method consisted of three stages: preparation, execution, and reporting. The activities included material presentation, practical sessions, group discussions, and question-and-answer sessions. The training covered waste sorting techniques, financial management of waste banks, and strategies for marketing recycled products. The results showed an improvement in participants’ understanding and motivation in managing waste systematically and productively. Additionally, participants demonstrated increased capability in organizing and documenting waste transactions, which contributes to enhancing their household income. Overall, this PKM activity successfully empowered the community to manage waste banks as sustainable social enterprises.